2019
DOI: 10.1186/s12913-019-4076-3
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening referral systems in community health programs: a qualitative study in two rural districts of Maputo Province, Mozambique

Abstract: Background Effective referral systems from the community to the health care facility are essential to save lives and ensure quality and a continuum of care. The effectiveness of referral systems in Mozambique depends on multiple factors that involve three main stakeholders: clients/community members; community health workers (CHWs); and facility-based health care workers. Each stakeholder is dependent on the other and could form either a barrier or a facilitator of referral within the complex heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 28 publications
(35 reference statements)
1
89
1
Order By: Relevance
“…An effective referral system is an indicator of a functional health system and can be a data source to understand how the community perceives the care they are receiving [32,33]. Strengthening the role of CHWs and empowered community engagement can be a key to improving the referral system [34]. Our study revealed that training midwives on basic emergency obstetric care in selected facilities would avoid serious complications and will ensure timely referral.…”
Section: Discussionmentioning
confidence: 90%
“…An effective referral system is an indicator of a functional health system and can be a data source to understand how the community perceives the care they are receiving [32,33]. Strengthening the role of CHWs and empowered community engagement can be a key to improving the referral system [34]. Our study revealed that training midwives on basic emergency obstetric care in selected facilities would avoid serious complications and will ensure timely referral.…”
Section: Discussionmentioning
confidence: 90%
“…The need for referral was explained to most of the caregivers, but referral notes were rarely provided. Lack of referral notes might have affected the continuity of care as information was not forwarded [27,28]. Non-adherence to referral guidelines was also observed among community health workers in Uganda [29] and Ghana [30] while a reasonable number of referrals supported with referral slips was observed among community health workers in Pakistan [27].…”
Section: Plos Onementioning
confidence: 99%
“…This is important in the referral process as poor knowledge on treatment availability may lead to incorrect or delayed referral to the secondary or tertiary govt. facilities, leading to poor health outcomes [10]. This again highlights the importance of the referral system.…”
Section: Assessment Of Knowledge About Cancermentioning
confidence: 99%
“…As of November 2018, 13779 CCs (one for every 6000 people) are operational, which are manned by 13507 CHCPs and 15420 HAs. From April 2009 to November 2018, there were 739.70 million visits by rural people to CCs all over Bangladesh and 13.229 million emergency and complicated cases were referred to higher facilities for better management [10]. This referral system is very important to ensure complicated cases are treated by the proper specialists [11].…”
Section: Introductionmentioning
confidence: 99%